Association between serum uric acid and atrial fibrillation: a cross-sectional community-based study in China. Issue 12 (22nd December 2017) - Chen, Yue; Xia, Yunlong; Han, Xu; Yang, Yiheng; Yin, Xiaomeng; Qiu, Jing; Liu, Henghui; Zhou, Yong; Liu, Ying
Abstract : Objectives: To investigate the effects of gender on the association of serum uric acid (SUA) levels and atrial fibrillation (AF) prevalence in a community-based Chinese population. Setting: Data were obtained from annual Jidong Oilfield employee and family member health checkups. The Jidong community is geographically located in Tangshan City in northern China. Participants: A total of 9078 residents were invited to take part in the survey and provided informed consents. Individuals without data of ECG or SUA were excluded, leaving 8937 residents in our study. Primary and secondary outcome measures: SUA was measured at baseline using the uricase-peroxidase method. Hyperuricaemia was defined as a SUA level >7.0 mg/dL in men and >5.7 mg/dL in women. AF was diagnosed based on ECG findings and/or any medical history of AF from referring physicians. The crude and independent association between SUA levels and AF prevalence was evaluated with logistic regression analysis. Results: AF prevalence was 0.6% (53/8937). Participants with hyperuricaemia had a higher AF prevalence compared with those with normal SUA levels (1.1% vs 0.5%; P=0.02). Hyperuricaemia was correlated with AF after adjustment for various cardiovascular risk factors in all participants (P=0.03, OR 2.051, 95% CI 1.063 to 3.856). This correlation was particularly stronger in women compared with men (P<0.001, OR 6.366, 95% CI 2.553 to 15.871 in women and P=0.96, OR 1.025, 95% CI 0.400 to 2.626 in men). Conclusions: We demonstrated a significant association between increased SUA levels and AF prevalence in a Chinese population. Our data indicate that there is a gender-specific mechanism underlying the relationship between SUA and AF.